Comparison of MRI Mismatch Criteria to Select Patients for Endovascular Stroke Therapy - Mishra, Nishant K (2014)
BACKGROUND AND PURPOSE: The DEFUSE 2 study has shown that the clinical response to endovascular reperfusion differs between patients with and without perfusion-diffusion (PWI-DWI) mismatch: patients with mismatch have a favorable clinical response to reperfusion whereas patients without mismatch do not. This study examined if alternative mismatch criteria can also differentiate patients according to their response to reperfusion. METHODS: Patients from the DEFUSE 2 study were categorized according to vessel occlusion on MRA and DWI lesion volume criteria (MRA-DWI mismatch) and symptom severity and DWI criteria (clinical-DWI mismatch). Favorable clinical response was defined as an improvement of ≥8 points on the National Institutes of Health Stroke Scale (NIHSS) by day 30 or an NIHSS score of ≤1 at day 30. We assessed, for each set of criteria, if the association between reperfusion and favorable clinical response differed according to mismatch status. RESULTS: A differential response to reperfusion was observed between patients with and without MRA-DWI mismatch defined as an ICA or M1 occlusion and a DWI lesion <50 mL. Reperfusion was associated with good functional outcome in patients who met these MRA-DWI mismatch criteria (OR 8.5; 95% CI 2.3–31.3), whereas no association was observed in patients who did not meet these criteria (OR 0.5; 95% CI 0.08–3.1) (p for difference between the odds = 0.01). No differential response to reperfusion was observed with other variations of the MRA-DWI or clinical-DWI mismatch criteria. CONCLUSIONS: The MRA-DWI mismatch is a promising alternative to DEFUSE 2's PWI-DWI mismatch for patient selection in endovascular stroke trials.